The Effect Of Information Quality And Trust On Cosumer Purchase Intention In E-Commerce Mediated By Psychological Distance And Moderated By Sense Of Power (Study On Shopee Application Users In Surabaya City) - Sinol Sinol; Bambang Setiyo Pambudi (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study aims to reveal and analyze the effect of information quality and trust on consumer purchase intentions mediated by psychological distance and moderated by sense of power (Study on Shopee application users in Surabaya City). This study uses quantitative methods with primary data and secondary data as supporting data. The writer's sampling technique used simple random sampling. In order to obtain data, the authors distributed questionnaires or questionnaires to Shopee application users in the city of Surabaya as many as 100 respondents who had made purchases through the Shopee application via the Facebook group.The data analysis technique of this research uses path analysis using SEM AMOS version 25.00 and SPSS version 25.00. The results of the study show that the quality of information has a positive and significant effect on trust, psychological distance has a positive and significant effect on trust, information quality has a positive and significant effect on trust, trust has a positive and significant effect on consumer purchase intentions and psychological distance mediates the relationship between information quality and trust. and a sense of power moderates the relationship between information quality and trust.